Modified Krasovskii's Method for Constructing Liapunov Function - Al-Bayaty, Intidhar Z Mushetet (Al-Nahrain Journal of Science, 2011)
In this paper, we modify the Krasovskii's method for constructing the Liapunov functions, which uses the numerical methods for solving ODE's to estimate the stability of systems via studying the stability of numerical method.